The socioimaginary construction of social protest in the discourse of the latin american press: analysis of the editorials of El Mercurio (Chile) and la nación (Argentina) newspapers in the context of the argentine crisis of 2001 (2018)
The present research work is proposed as a space for theoretical discussion and empirical analysis around the problematic of the power of the media in contexts of social conflict. Explicitly, this paper aims to analyze the socioimaginary construction of social protest in the editorial discourse produced by El Mercurio (Chile) and La Nación (Argentina) newspapers, based on the popular demonstrations that took place during December 2001 in the framework of the economic crisis in Argentina. To answer our research question and meet the goal of the study, we used a discourse analysis model that was applied to a corpus of 40 leading articles, selected from a sample of 80 journalistic texts published by El Mercurio and La Nación from December 1, 2001 to March 31, 2002. The main findings of the research regarding the mobilizations that took place in the context of the economic crisis in Argentina allow us to show that both newspapers built an imaginary of social protest that was based on a discourse with four categories: Civilization, barbarism, exclusion, and inclusion. Therefore, El Mercurio and La Nación newspapers not only made visible in the public space the events associated with the protests of December 2001, but also, these media channeled, through their leading articles, explanations about the conflict. They also participated in the public debate regarding collective protest actions, constructed representations and imaginary articulations about the events and social actors that participated in the interactions framed in the conflict, and, of course, assumed an ideological position in their quality of actors of the political system regarding the economic crisis and the social conflict that happened in the Argentine society during 2001.